CaMKII delta interaction with neuronal sodium channel Nav1.8 contributes to arrhythmogenic triggers in failing human and mouse cardiomyocytes. (25th November 2020) - Dybkova, N; Ahmad, S; Tirilomis, P; Bengel, P; Pabel, S; Maier, L.S; Hasenfuss, G; Sossalla, S
Abstract:  : In heart failure, enhanced persistent current through neuronal sodium channel NaV1.8 (INaL) may induce influx of Na+ into cardiomyocytes. This may cause Ca2+ influx via the Na+/Ca2+ exchanger leading to increased proarrhythmogenic diastolic sarcoplasmic reticulum (SR) Ca2+ leak. This Ca2+ may activate Ca2+/calmodulin-dependent protein kinase IIδ (CaMKIIδ) which can induce INaL augmentation by phosphorylating NaV1.5 channels leading to a vicious cycle between INaL and CaMKIIδ. Here, we examined whether CaMKIIδ associates with NaV1.8 in human and mouse cardiomyocytes thereby regulating its function. Interaction and co-localisation of CaMKIIδ and NaV1.8 were confirmed by co-immunoprecipitation and immunocytochemistry. Whole-cell patch clamp showed a potent reduction of INaL after addition of novel specific Nav1.8 blockers, either A-803467 (30 nmol/L) or PF-01247324 (1 μmol/L) in failing mouse cardiomyocytes overexpressing CaMKIIδc (CaMKIIδc+/T: −109.4±10.6 vs A-803467: −56.9±11.7 and PF-01247324:−-69.9±8.6 A*ms*F-1). In failing human cardiomyocytes inhibition of either NaV1.8 or CaMKIIδ using AIP (1 μmol/L) or AIP and PF-01247324 together led to a significant and comparable decrease of INaL (control: −93.7±7.1 vs PF-01247324: −56.8±6.6; AIP: −44.2±6.6; AIP+PF-01247324: −39.8±5.4 A*ms*F-1). Furthermore, to confirm whether observed alterations in INaL after inhibition of NaV1.8 are not due to an overall reduction in peak sodium current (INa) we measured INa properties in mouse cardiomyocytes. Importantly, we observed no difference neither in the peak nor in inactivation between wild type (WT), WT with PF-01247324 and in mice lacking NaV1.8. Using confocal microscopy we investigated whether inhibition of the NaV1.8-mediated INaL could attenuate the increase of proarrhythmogenic SR Ca2+ spark frequency (CaSpF) caused by overexpression of CaMKIIδ in mice. We observed a significant reduction of CaSpF in both NaV1.8 inhibitor groups (PF-01247324: 0.51±0.08 and A-803467: 0.57±0.08 μm –1 s –1 ) compared to control (1.00±0.13 μm –1 s –1 ). Incubation of human failing cardiomyocytes with either AIP (0.35±0.06 μm –1 s –1 ) or PF-01247324 (0.44±0.11 μm –1 s –1 ), or blocking CaMKIIδ and NaV1.8 together (0.30±0.08 μm –1 s –1 ) resulted in significant decrease of CaSpF compared to control (0.89±0.13 μm –1 s –1 ). In conclusion, we show for the first time subcellular localisation of the neuronal sodium channel NaV1.8 and its interaction with CaMKIIδ in both human and mouse ventricular cardiomyocytes. Moreover, pharmacological inhibition of NaV1.8 caused a reduction of the augmented INaL and spontaneous diastolic SR-Ca2+ release in both failing human and mouse cardiomyocytes. NaV1.8 and CaMKIIδ interaction seem to play a relevant role for the generation of arrhythmogenic triggers (INaL & spontaneous diastolic SR-Ca2+ release) in both human and mouse cardiomyocytes from failing hearts. Funding Acknowledgement: Type of funding source: None